Cholesterol metabolism, LDL, and the LDL receptor - Myant, N. B. (Academic Press, 1990)
Cholesterol Metabolism, LDL, and the LDL Receptor focuses on the cholesterol biochemistry and lipoprotein metabolism. This book is organized into 10 chapters that describe the coordinated actions of three regulated processes, namely, the intracellular synthesis of cholesterol, its esterification by ACAT, and the receptor-mediated uptake of low-density lipoprotein (LDL), for optimal level of free cholesterol. The first five chapters explore the various aspects of cholesterol biology, including discussions on the interaction of ligands with their cell-surface receptors; the role of coated pi.